Ground deformation measurements over Lake Trichonis based on SAR interferometry. - Benekos, G.; Parcharidis, I.; Foumelis, M.; Ganas, A. (Bulletin of the Geological Society of Greece, 2013)
The aim of this study is to detect and measure ground deformation over the broader area of Lake Trichonis (Western Greece), focusing mainly on the April 2007 earthquake swarm which occurred at the vicinity of the Lake. The area, forming a pull-apart basin, presented historically an intense seismic activity along the two active normal faults at the northern and southern part of the Lake. The swarm initiated by small magnitude events on the 8th of April 2007 followed by the three strongest events of the entire sequence on the 10th of April 2007, with magnitudes ranging from 5.0 to 5.2 Mw. The seismic activity continued for longer with smaller seismic events. Based on seismological data this activity was attributed to two unmapped NW SE trending normal faults that bounds the SE bank of the Lake. Using a dataset of 28 ENVISAT ASAR scenes covering the period from February 2003 until February 2010 (~7 yr), different Interferometric Stacking techniques was applied in order to quantify the ground deformation induced by the earthquake swarm as well as its effect on the inter-seismic deformation pattern of the area. Our results indicate that co-seismic motion differs significantly from that observed during the pre- and post- swarm periods. The co-seismic pattern reveals subsidence at the northern and uplift at the southern lake sides, consistent with the structural model already proposed for the area. For the pre- and post-seismic periods both sides of the Lake show stability or low rates of subsidence with higher deformation velocity rates for the period after the seismic activity, possibly attributed to postseismic relaxation. Our findings imply that inter-seismic ground deformation does not necessary follow the deformation pattern observed during seismic triggering, thus, long-term geodetic observations such as those provided by SAR interferometry are valuable in order to fully characterize the geodynamic behavior of an active region.